Case Report: A Mysterious Giant Thrombus in the Right Atrium in a Patient With Dilated Cardiomyopathy - Lian, Ping-an; Long, Xia; Zhu, Wen-qiang; Huang, Xian-sheng (Frontiers in Cardiovascular Medicine, 2022)
An isolated right atrial thrombus is a life-threatening entity that is extremely rare in patients with dilated cardiomyopathy (DCM), which is characterized by a reduced left ventricular function and consequent left ventricular thrombosis. Here, we present the case of a mysterious isolated giant right atrial thrombus in a male patient with DCM. The presence of deep vein thrombosis prompted us to investigate for other underlying diseases for his right atrial thrombus. Interestingly, the elevation of two tumor markers indicated the likelihood of cancer-associated thrombosis. Further, computed tomography demonstrated a spiculated mass in the lower right lung that was confirmed by an endobronchial biopsy as lung squamous cell carcinoma. Consequently, the giant thrombus in the right atrium resulted from the patient’s thrombophilic state caused by lung cancer instead of DCM. The protracted diagnostic process of this patient emphasized the necessity of identifying another underlying non-cardiac disease in cases of unexplained intracardiac thrombosis.